Collecting Contemporary Art. - Arkio, Tuula; Baekeland, Frederick; Blomerus, Inge; Haapala, Arto; Harri, Juhani; Ketonen, Helka; Kouri, Pentti; Levanto, Yrjänä; Olof Mallander, Jan; Peltola, Leena; Pettersson, Susanna; Rantala, Kati; et al. (Helsinki : Finnish National Gallery Helsinki, 1999)
The Finnish National Gallery's new Museology series opens up new critical viewpoints on accepted artmuseum practices and their importance to society. This first volume provides an opportunity for a broad inquiry into the collecting of contemporary art and its consequences. It includes the latest research from researchers on art history museology, aesthetics and sociology. It also addresses the psychology of art collecting. The articles analyse major issues in art collecting : the reasons why and how works are chosen for different collections, the contexts of the work plus what happens to a work when it becomes part of a public collection. There are also previously unpublished interviews in which we hear from public and private collections of art.
Engels
Fins
boek
Keywords: Finland